Hubungan antara pola pemberian makan dengan kejadian wasting pada balita usia 12-59 bulan di Kabupaten Banggai Sulawesi Tengah - Apiani, Afiqah Nur; Salam, Abdul; Hidayanty, Healthy; Hadju, Veni; Mansur, Marini Amalia (ARGIPA (Arsip Gizi dan Pangan), 2024)
Wasting is still a widespread nutritional problem. Wasting refers to a state of acute malnutrition resulting from body weight that is disproportionate to body size or height. The cause of wasting is acute hunger due to lack of nutrition through feeding patterns. The aim of this research is to understand the relationship between feeding patterns and the incidence of wasting in toddlers aged 12-59 months in Banggai Regency, Central Sulawesi. The research was carried out from July to August 2023 in the working areas of the Toili I Health Center and the Sinorang Health Center. The method used is quantitative with a cross-sectional design. Samples were taken using purposive sampling with the number of subjects being 172 toddlers who had experienced wasting. Data were collected using the Child Feeding Questionnaire and anthropometric measurements (BB, TB/PB, and LiLA). The chi-square test was used in data analysis. The research results showed that 25% of toddlers experienced wasting and most mothers (62.2%) had appropriate feeding patterns. In terms of types of food, 59.3% of mothers rarely provide food sources of vitamins, and in terms of meal schedules, 62.7% of mothers rarely provide snacks and 73.8% of mothers rarely provide fruit and vegetables. This research concludes that there is a relationship between feeding patterns and the incidence of wasting in toddlers aged 12-59 months in Banggai Regency, Central Sulawesi. In subjects experiencing wasting, there were more inappropriate feeding patterns found at 33.8%. On the other hand, subjects who did not experience wasting were more likely to get the right feeding pattern by 80.4%. So it is hoped that mothers can improve various skills and knowledge that focus on responsive feeding eating.